Hydrothermal carbonization (HTC) of selected woody and herbaceous biomass feedstocks - Hoekman, S. Kent; Broch, Amber; Robbins, Curtis; Zielinska, Barbara; Felix, Larry (Biomass conversion and biorefinery, 2013)
A hydrothermal carbonization (HTC) process was applied to six biomass feedstocks—three woody and three herbaceous. Each feedstock was treated in liquid water for 30 min at temperatures ranging from 175 to 295 °C. Gaseous, aqueous, and solid hydrochar products were characterized to examine the effects of process temperature upon product yields, compositions, and energy densification. Thorough mass balance determinations were made for all HTC experiments. With increasing temperature, the mass of solid hydrochar products was reduced, but energy density increased. At temperatures ≥255 °C, hydrochars produced from woody feedstocks had energy contents of 28–30 MJ/kg, comparable to subbituminous coal. Hydrochars produced from herbaceous feedstocks had somewhat lower energy contents. With increasing temperature, the atomic O/C ratio of all samples was reduced from 0.6 to 0.7 in the raw feedstocks to approximately 0.2 in the hydrochars. Gaseous products increased with increasing HTC temperature, reaching 10–12 % at ≥275 °C. The sum of sugar and organic acid yields was typically 8–12 %, although the composition of these aqueous products varied with temperature. Water was produced in yields of 10–20 % at process temperatures of ≥255 °C.